2021
DOI: 10.3389/fcvm.2021.633631
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Transcriptome-Wide m6A Methylome of Heart via MeRIP After Birth: Day 0 vs. Day 7

Abstract: Aim: To systematically classify the profile of the RNA m6A modification landscape of neonatal heart regeneration.Materials and Methods: Cardiomyocyte proliferation markers were detected via immunostaining. The expression of m6A modification regulators was detected using quantitative real-time PCR (qPCR) and Western blotting. Genome-wide profiling of methylation-modified transcripts was conducted with methylation-modified RNA immunoprecipitation sequencing (m6A-RIP-seq) and RNA sequencing (RNA-seq). The Gene Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
0
20
1
Order By: Relevance
“…In this study, we identified 27,292 m6A peaks in OVA-induced lung tissues. Most of these m6A peaks were distributed in the 3' UTR and exon regions, which is inconsistent with the previously reported peak distribution trend in mouse liver ( 46 ), sheep liver ( 47 ), rat heart ( 48 ), and human tumor tissue ( 49 , 50 ). We considered that such inconsistencies may be related to different species, tissues, and conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we identified 27,292 m6A peaks in OVA-induced lung tissues. Most of these m6A peaks were distributed in the 3' UTR and exon regions, which is inconsistent with the previously reported peak distribution trend in mouse liver ( 46 ), sheep liver ( 47 ), rat heart ( 48 ), and human tumor tissue ( 49 , 50 ). We considered that such inconsistencies may be related to different species, tissues, and conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…As the core component of the methyltransferase complex, METTL3 is the catalytic subunit of this complex, and it plays a negative role with METTL14 in maintaining RNA stability and cell self-renewal capacity by mediating m6A modification [33]. Our previous study, which included genome-wide analyses of m6Amodified transcripts, showed that increased METTL3 expression may enhance the proliferative capacity of neonatal cardiomyocytes [14]. A novel study found that increased METTL3 levels are beneficial for preserving the physiological cardiomyocyte morphology that helps maintain normal cardiac output, whereas disrupted METTL3 expression may induce abnormal cardiomyocyte remodeling and cardiac dysfunction [13]; these findings indicate that the dynamic modification of METTL3-mediated m6A methylation plays a vital role in the adaptive response of the myocardium to various physiological and pathological stimuli by regulating gene expression programs [13], suggesting a key role for METTL3 in the heart and the potential therapeutic benefit of targeting this pathway to treat pathological cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dorn et al demonstrated that the dynamic homeostasis of methyltransferase-like 3 (METTL3) is essential for normal cardiomyocyte hypertrophy [13]. Our most recent study using methylation-modified RNA immunoprecipitation sequencing (m6A-RIP-seq) and RNA sequencing (RNA-seq) also suggested that METTL3 is necessary to maintain the proliferative capacity of neonatal cardiomyocytes after birth [14]. However, our knowledge about the biological function of METTL3 in regulating cardiomyocyte proliferation after MI injury is still limited.…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, accumulating evidence showed that the m 6 A level is closely related to the development of heart disease; for example, METTL3 overexpression can induce eccentric remodeling and cardiac dysfunction alone without an additional stressor [19]. m 6 A is also involved in the process of myocardial regeneration [16][17][18]. It has previously been documented that compared with normal heart tissue, the level of m 6 A modification is higher and FTO expression level is lower in myocardium tissue of mice with ischemic damage and heart failure [50].…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A modification reflects a dynamic and reversible process, which involves methyltransferases (METTL3, METTL14 and WTAP), demethylases (FTO, ALKBH5 and ALKBH3) and RNA-binding proteins (YTHDF1-3, YTHDC1-2 and IGF2BPs) processing [15]. A previous study showed that METTL3 was downregulated in the postnatal day (P7) relative to P0 heart in rat newborns, and enhancing METTL3 expression level of P0 cardiomyocytes resulted in increased proliferation in vitro [16]; however, in opposition to this, a recent study showed identified global METTL3 knockout enhanced cardiac regeneration and repair after myocardial injury [17]. It was also reported that m 6 A methylation was significantly increased and the expression level of ALKBH5 was decreased after birth in the mouse heart and its overexpression promoted myocardial regeneration and repair after the myocardial infarction (MI) [18].…”
Section: Introductionmentioning
confidence: 99%